Community diagnosis in oshakati, oshana region -Namibia - Mitonga, Kabwebwe Honore; Mwikume, Banza FranÃ§oise; Anna Panduleni Kauko, Shilunga (International Journal of Medicine, 2017)
This paper aimed to diagnose the community of Oshakati community in Oshana region in the northern part of the Republic of Namibia by providing an overall picture of the local community and the residentsâ€™ concerns, the health problems and challenges and suggest priority areas for health intervention and the feasible solutions.A survey was conducted using self-administered questionnaires, face to face interviews, focus groups.The main problems identified are: teenage pregnancies due to unprotected sex and early sexual behaviors, promiscuity by means of poverty, alcohol and drug abuse resulting in stab wounds, uncontrolled behaviors, domestic violence, assault and crime, high levels of unemployment, stress and depression, TB, HIV with growing number of orphans, diarrhea and respiratory infections.The survey conducted in Oshakati has shown that the assessment of the community is useful in identifying the important problems and needs for the community; the cultural, social, economic, environmental factors have to be considered for good health reform. The resources are available and should be utilized for active participation of the people and implication of the authorities in health promotion by identifying and prioritizing problems of the community they serve.